2016
DOI: 10.1021/acssuschemeng.6b00314
|View full text |Cite
|
Sign up to set email alerts
|

Two-in-One Fuel Combining Sewage Sludge and Bioliquid

Abstract: In this study, we first proposed hybrid sludge as a two-in-one fuel combining bioliquid (molasses and glycerol) with digested sewage sludge. The hybrid sludge is easily prepared by impregnation of sludge with bioliquid, and drying (or carbonization). After drying and carbonization treatment below 250 °C, the embedded bioliquid plays an important role as a artificial volatile matter or fixed carbon, which improves the calorific value of hybrid sludge. The hybrid sludge is denoted as hybrid sewage sludge by Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…However, the combustion pattern of the hybrid coals (BC) was changed from a multistage combustion pattern to a single combustion pattern through the addition of glycerol and the torrefaction process (changes the chemical properties of the volatile matter). In addition, like the previously reported HCK , ,, we observed homogeneous combustion behavior (so-called two-in-one fuel) of the glycerol/carbonized hybrid coals regardless of glycerol content from 10 to 30%, from which we deduce that the carbons from the glycerol with sulfuric acid during torrefaction becomes unified with the carbons inside raw coals; thus, they fill the inherent pores of raw coals. In fact, the infiltration and carbonization mechanism of glycerol inside carbonic pores has been previously reported. Direct evidence to support this deduction was also obtained by a nitrogen sorption test; the results for the raw coal after drying (BC-D) and hybrid coals are summarized in Figure and Table .…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the combustion pattern of the hybrid coals (BC) was changed from a multistage combustion pattern to a single combustion pattern through the addition of glycerol and the torrefaction process (changes the chemical properties of the volatile matter). In addition, like the previously reported HCK , ,, we observed homogeneous combustion behavior (so-called two-in-one fuel) of the glycerol/carbonized hybrid coals regardless of glycerol content from 10 to 30%, from which we deduce that the carbons from the glycerol with sulfuric acid during torrefaction becomes unified with the carbons inside raw coals; thus, they fill the inherent pores of raw coals. In fact, the infiltration and carbonization mechanism of glycerol inside carbonic pores has been previously reported. Direct evidence to support this deduction was also obtained by a nitrogen sorption test; the results for the raw coal after drying (BC-D) and hybrid coals are summarized in Figure and Table .…”
Section: Results and Discussionsupporting
confidence: 89%
“…In addition, like the previously reported HCK , ,, we observed homogeneous combustion behavior (so-called two-in-one fuel) of the glycerol/carbonized hybrid coals regardless of glycerol content from 10 to 30%, from which we deduce that the carbons from the glycerol with sulfuric acid during torrefaction becomes unified with the carbons inside raw coals; thus, they fill the inherent pores of raw coals. In fact, the infiltration and carbonization mechanism of glycerol inside carbonic pores has been previously reported. Direct evidence to support this deduction was also obtained by a nitrogen sorption test; the results for the raw coal after drying (BC-D) and hybrid coals are summarized in Figure and Table . While the pore size of BC-D generally ranged between 2 and 6 nm, we observed that the pore area and pore volume were significantly reduced by 96% regardless of the glycerol/coal weight ratio.…”
Section: Results and Discussionsupporting
confidence: 89%
“…When the results are expressed by the atomic ratio (H/C and O/C ratio), it can be seen that the ratio value gradually decreased as the pretreatment temperature increased. According to the literature [22], the higher the carbonization degree is, the lower the ratio of H/C and O/C will be. During the wet torrefaction process, dehydration, decarboxylation, and demethanation result in high quality fuel.…”
Section: Fuel Properties Of Wt Samplesmentioning
confidence: 99%
“…The activated sludge process is an extensively employed wastewater treatment process as a result of its efficiency in nutrient removal; however, the main problem is the generation of a large quantity of waste activated sludge in recent years. , This excess quantity of sludge produces a serious menace to human health and the surroundings . Anaerobic digestion (AD) is broadly applied for bioenergy recovery and stabilization of sludge. In AD of sludge, hydrolysis is considered as the rate-limiting phase, and this aspect needs more research and attention .…”
Section: Introductionmentioning
confidence: 99%